Economic challenges of post-tsunami reconstruction in Sri Lanka - Dushni Weerakoon; Sisira Jayasuriya; Nisha Arunatilake; Paul Steele (Asian Development Bank Institute (ADBI), 2007)
After successful emergency relief operations, Sri Lanka initiated post-tsunami reconstruction with optimism and a relatively rapid recovery was expected. However, initial expectations have turned out to be overly optimistic. Coordination problems between agencies, constraints on aid absorption capacity, and inequities in aid distribution among regions have hampered reconstruction. Infrastructure reconstruction targets have not been fully met. Initial expectations that the tsunami experience would lead to peace were not fulfilled, inequitable distribution exacerbated mistrust, and largescale conflict has resumed. Macroeconomic management and efficient absorption of a large, necessarily temporary, inflow of foreign funds has been a daunting task. Construction costs rapidly escalated, producing unanticipated funding gaps and aggravating fiscal deficit problems. Sri Lanka's experience highlights the need for anticipating such cost increases when assessing needs following major disasters, as well as the need for formulation of a phased programme of reconstruction which takes into account the supply side constraints of construction inputs.
Keywords: Q54; F35; H54; I38; O19; 330; Überschwemmung; Katastrophenschaden; Wirtschaftliche Anpassung; Sri Lanka